HCAR1/MCT1 Regulates Tumor Ferroptosis through the Lactate-Mediated AMPK-SCD1 Activity and Its Therapeutic Implications - Zhao, Youbo; Li, Menghuan; Yao, Xuemei; Fei, Yang; Lin, Zhenghong; Li, Zhengguo; Cai, Kaiyong; Zhao, Yanli; Luo, Zhong (Cell reports (Cambridge), 2020)
Ferroptosis is a recently discovered form of programed cell death caused by the metabolically regulated lipid peroxidation and holds promise for cancer treatment, but its regulatory mechanisms remain elusive. In this study, we observe that lactate-rich liver cancer cells exhibit enhanced resistance to the ferroptotic damage induced by common ferroptosis inducers such as Ras-selective lethal small molecule 3 (RSL3) and Erastin and that the monocarboxylate transporter 1 (MCT1)-mediated lactate uptake could promote ATP production in hepatocellular carcinoma (HCC) cells and deactivate the energy sensor AMP-activated protein kinase (AMPK), leading to the upregulation of sterol regulatory element-binding protein 1 (SREBP1) and the downstream stearoyl-coenzyme A (CoA) desaturase-1 (SCD1) to enhance the production of anti-ferroptosis monounsaturated fatty acids. Additionally, blocking the lactate uptake via hydroxycarboxylic acid receptor 1 (HCAR1)/MCT1 inhibition promotes ferroptosis by activating the AMPK to downregulate SCD1, which may synergize with its acyl-coenzyme A synthetase 4 (ACSL4)-promoting effect to amplify the ferroptotic susceptibility. In vitro and in vivo evidence confirms that lactate regulates the ferroptosis of HCC cells and highlights its translational potential as a therapeutic target for ferroptosis-based tumor treatment. [Display omitted] •Lactate uptake promotes ATP production to upregulate SREBP1 and SCD1•Lactate mediates the production of ferroptosis-related lipids in cancer cells•HCAR1/MCT1 inhibition sensitizes cancer cells to ferroptosis induction Zhao et al. discover a lactate-mediated ferroptosis regulatory pathway in liver cancer cells, through which lactate enhances their ferroptosis resistance by upregulating the production of anti-ferroptosis monounsaturated fatty acids. Their findings may provide avenues for the development of ferroptosis-based cancer therapies.